A Hiplot‐based web service for cold atmospheric plasma high‐throughput data integration and analysis on breast cancer - Xiaofeng Dai; Mingjie Wang; Yang Liu (iMeta)
Abstract Incremental evidence on the effect of cold atmospheric plasma (CAP) in specifically killing transformed cells and advances in sequencing technologies at multiple omics have led to the demand of in‐depth exploration on the mechanisms of action driving the potency of CAP against cancer cells at the molecular level. However, high‐throughput data detailing the effect of CAP on cancer cells is lacking, let alone the corresponding database and analytical tool. Here, we sequenced the whole transcriptome, proteome, phosphorylome, acetylome, and lactylome of transformed cells in response to CAP using breast cancer cells as the disease model; and advanced our previously developed Hiplot platform by establishing a focus‐driven tumor‐specific module, namely CAP medicine in breast cancer (CAPmed‐BC) (https://capbc.hiplot.com.cn). CAPmed‐BC is the first multi‐omics data resource in plasma medicine for analyzing the treatment response of breast cancer cells to CAP. It can analyze each type of omics data regarding differentially expressed biomarkers, expression landscape, gene ontology analysis, pathway interpretation, gene set enrichment analysis, and protein‐protein interaction network. It can also interrogate the dynamic fluctuation, functional activity, and metabolic vulnerability of cancer cells in response to CAP by combinatorially analyzing omics at multiple carefully defined dimensions. We also built in a visualization module to support users for producing personalized graphs via adjusting parameters. We believe that CAPmed‐BC will become a valuable resource for characterizing the outcome of CAP on breast cancers at the omics and molecular levels, and make considerable contributions to both plasma medicine and oncology.